2017
DOI: 10.1371/journal.pone.0168883
|View full text |Cite
|
Sign up to set email alerts
|

Critical Size Bone Defect Healing Using Collagen–Calcium Phosphate Bone Graft Materials

Abstract: The need for bone graft materials to fill bony voids or gaps that are not related to the intrinsic stability of the bone that arise due to trauma, tumors or osteolysis remains a clinically relevant and significant issue. The in vivo response of collagen–tricalcium phosphate bone graft substitutes was evaluated in a critical size cancellous defect model in skeletally mature rabbits. While the materials were chemically virtually identical, new bone formation, implant resorption and local in vivo responses were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 61 publications
(61 reference statements)
0
49
0
7
Order By: Relevance
“…Typically, defects are created in a weight-bearing region of the sheep bone, which provides similarities in bone composition, defect size and healing rate compared to humans 36,38 . Critical defects models generally evaluate the in vivo performance of biomaterials in terms of bone regeneration, remodelling, biomaterial resorption and biological effects 35,39,40 .…”
Section: Introductionmentioning
confidence: 99%
“…Typically, defects are created in a weight-bearing region of the sheep bone, which provides similarities in bone composition, defect size and healing rate compared to humans 36,38 . Critical defects models generally evaluate the in vivo performance of biomaterials in terms of bone regeneration, remodelling, biomaterial resorption and biological effects 35,39,40 .…”
Section: Introductionmentioning
confidence: 99%
“…While the in vitro characterisation of CelGro™ showed that CelGro™ contains relatively pure type I collagen bundles and display less deformity and better mechanical strength, we next conducted a preclinical study to determine the efficacy of CelGro ™ for GBR in the repair of diaphysis cortical bones defects in rabbits. Previously, it has been shown that healing of a standard-sized defect in rabbit femoral bone treated with bone autograft occurs between 30 to 60 days after surgery (22) (23). To evaluate the efficacy of collagen membranes in conjunction At 30 days after surgery, the effect of a collagen membrane could be clearly observed by micro-CT (Fig.…”
Section: Regeneration Of Cortical Bone Defects In a Rabbit Modelmentioning
confidence: 99%
“…Ex vivo evaluation of bone regeneration is conducted at one unique time point and it usually involves histology, SEM and XCT investigations (Coathup et al, 2008;Wang et al, 2015;Machado et al, 2016;Walsh et al, 2017;. The three techniques are complimentary and combined provide a deep insight on bone formation in the defect site.…”
Section: Ex Vivo Analysis Of Bone Regenerationmentioning
confidence: 99%
“…On the other hand, cranial-defect models lack from weight-bearing and, therefore, their clinical relevance may be questioned due to the absence of loading that can affect the potential bone formation capacity of the biomaterials (Cowan et al, 2004;Pound et al, 2006;Bolland et al, 2008;Dawson et al, 2008;Kisiel et al, 2013). Large animal models, such as femoral condyle-defect models in rabbits or sheep circumvent some of that shortcomings, as defects are created in a weight-bearing region and no fixators are needed (Walsh et al, 2003;Fini et al, 2005;Ueng et al, 2007;Malhotra et al, 2014;Pobloth et al, 2016;Walsh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%